Analysis of The Service System In The General Poly RS Husada Utama With Discrete Simulation - Alisa Audria Fadillah, Pinkkan; Sayid Albana, Abduh; Arismawati, Paramaditya (eProceedings of Engineering, 2025)
Hospitals require high efficiency, with one major challenge being the management of patient queues. At Husada Utama Hospital, long queues lead to waiting times of up to 90 minutes due to an imbalance between patient arrivals and service capacity. This study aims to reduce waiting times and improve service levels by modeling the queuing system using discrete simulation. Observation data from 08.00 to 17.00 on busy days (excluding special holidays) were used, processed, and simulated using Arena Software. Model verification and validation were conducted by comparing simulation results with actual data through T-tests. Under current conditions, the average waiting time at the Nurse Station is 47.86 minutes (72% utility), at the General Poly 144.86 minutes (89%), and at the Specialist Poly 163.97 minutes (89%). After applying improvement scenario 1, which adds one APKM unit, waiting times dropped to 26.80 minutes (68% utility) at the Nurse Station, 94.03 minutes (83%) at the General Poly, and 105.23 minutes (84%) at the Specialist Poly. This represents a reduction in waiting time of 60.82%, 35.08%, and 35.83% respectively. Scenario 1 is proven to be the most effective in reducing average waiting times with optimal utility. Kata kunci— Queue, Arena, Hospital, Discrete Simulation